Open Approaches to the Anterior Skull Base in Children: Review of the Literature - Wasserzug, Oshri; DeRowe, Ari; Ringel, Barak; Fishman, Gadi; Fliss, Dan M. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction Skull base lesions in children and adolescents are rare, and comprise only 5.6% of all skull base surgery. Anterior skull base lesions dominate, averaging slightly more than 50% of the cases. Until recently, surgery of the anterior skull base was dominated by open procedures and endoscopic skull base surgery was reserved for benign pathologies. Endoscopic skull base surgery is gradually gaining popularity. In spite of that, open skull base surgery is still considered the “gold standard” for the treatment of anterior skull base lesions, and it is the preferred approach in selected cases.Objective This article reviews current concepts and open approaches to the anterior skull base in children in the era of endoscopic surgery.Materials and Methods Comprehensive literature review.Results Extensive intracranial–intradural invasion, extensive orbital invasion, encasement of the optic nerve or the internal carotid artery, lateral supraorbital dural involvement and involvement of the anterior table of the frontal sinus or lateral portion of the frontal sinus precludes endoscopic surgery, and mandates open skull base surgery. The open approaches which are used most frequently for surgical resection of anterior skull base tumors are the transfacial/transmaxillary, subcranial, and subfrontal approaches. Reconstruction of anterior skull base defects is discussed in a separate article in this supplement.Discussion Although endoscopic skull base surgery in children is gaining popularity in developed countries, in many cases open surgery is still required. In addition, in developing countries, which accounts for more than 80% of the world's population, limited access to expensive equipment precludes the use of endoscopic surgery. Several open surgical approaches are still employed to resect anterior skull base lesions in the pediatric population. With this large armamentarium of surgical approaches, tailoring the most suitable approach to a specific lesion in regard to its nature, location, and extent is of utmost importance.
Keywords: skull base; children; open approaches; subcranial approach; reconstruction